Hydrogen production in a Pore-Plated Pd-membrane reactor: Experimental analysis and model validation for the Water Gas Shift reaction. (2nd March 2015) - Sanz, R.; Calles, J.A.; Alique, D.; Furones, L.; Ordóñez, S.; Marín, P.
Abstract A laboratory reactor equipped with a Pd-composite membrane prepared by ELP "pore-plating" method (Pd thickness of 10.2 μm) has been used for performing the water gas shift reaction (WGSR). Reaction experiments were carried out with and without the membrane at different operating conditions: H2O/CO ratio (1–3), temperature (350–400 °C) and GHSV (4000–5500 h−1). In all cases, CO conversion was found to be higher when using the membrane to separate hydrogen. The membrane maintained the integrity with complete selectivity to H2. The membrane reactor has been modelled using a 2D mathematical model, capable of modelling the non-ideal flow pattern formed in this type of reactors. The model predicts the experimental CO conversion with an accuracy of ±10%. The proposed model was used as a tool in the scale-up of a membrane reactor for the water–gas-shift reaction (feed: 100 m3/h synthesis gas), designed to achieve high CO conversion (>99%) and hydrogen recovery (>99.5%). The permeation of hydrogen through the membrane was found to be ruled by mass transfer in the membrane support and palladium layer.